2013
DOI: 10.1007/s11661-013-2114-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Irradiated Metal Waste from the Pyrometallurgical Treatment of Used EBR-II Fuel

Abstract: As part of the pyrometallurgical treatment of used Experimental Breeder Reactor-II fuel, a metal waste stream is generated consisting primarily of cladding hulls laden with fission products noble to the electrorefining process. Consolidation by melting at high temperature [1873 K (1600°C)] has been developed to sequester the noble metal fission products (Zr, Mo, Tc, Ru, Rh, Te, and Pd) which remain in the iron-based cladding hulls. Zirconium from the uranium fuel alloy (U-10Zr) is also deposited on the hulls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Westphal and co-workers at INL reported the development and characterisation of the first production-scale irradiated metal waste ingot in 2015, produced from used EBR-II fuel using a vacuum induction furnace in the Materials and Fuels Complex Hot Fuel Examination Facility [85]. The ingot contained Fe-based fuel cladding with NMFPs (Mo, Ru, Rh, Tc, Pd, and Te), as well as U and Zr from fuel adhering to the cladding.…”
Section: Waste Form Options For Metal Waste Streamsmentioning
confidence: 99%
“…Westphal and co-workers at INL reported the development and characterisation of the first production-scale irradiated metal waste ingot in 2015, produced from used EBR-II fuel using a vacuum induction furnace in the Materials and Fuels Complex Hot Fuel Examination Facility [85]. The ingot contained Fe-based fuel cladding with NMFPs (Mo, Ru, Rh, Tc, Pd, and Te), as well as U and Zr from fuel adhering to the cladding.…”
Section: Waste Form Options For Metal Waste Streamsmentioning
confidence: 99%
“…This process has been developed and deployed for DOE sodium bonded fuel treatment at Idaho National Laboratory as described in the Metal Waste Form Handbook (Abraham et al 1999) and demonstrated full scale as described in Characterization of Irradiated Metal Waste from the Pyrometallurgical Treatment of Used EBR-II Fuel. (Westphal et al 2013) The process and qualification activities for this waste form are all based on 316 SS based fuel cladding, while the reference (and most likely) cladding for FR fuel is HT-9. The research needs include 1.…”
Section: Metal Wastementioning
confidence: 99%
“…Larger 60-kg ingots have been produced as part of a waste form qualification effort (Frank et al 2007). A full-scale ingot of 43.2 kg was recently produced with actual metal fuel cladding wastes (Westphal et al 2013).…”
Section: Stainless-steel-based Alloysmentioning
confidence: 99%